A DESCRIPTIVE COMPARISON OF LANGUAGE POLICIES USING COBARRUBIAS’ LANGUAGE IDEOLOGIES: THE CASE OF SINGAPORE AND TIMOR-LESTE - Alican Mendez Pandapatan (Journal of Language, Literature and Teaching, 2026)
Language policy is mediated by the socio-politico-historical background of the society. It directs people to integrate and unify themselves to the vision of the governments towards progress, which includes education per se. This study compared Singapore and Timor-Leste, with quite similar backgrounds yet different implementation of policies as a result of each nation’s linguistic ideologies. A qualitative comparative design was employed in this study, using Cobarrubias’ Language Ideologies as a framework for comparison. Secondary materials are resourced as data. It is revealed the ideological concepts in the studied nations. In linguistic assimilation, Singapore did not employ the assimilation except for certain provisions in the government, and Timor-Leste had to assimilate minor languages due to the stronghold of dominant languages. For vernacularization, Singapore is accommodative to all linguistic groups, and Timor-Leste is fragmented to its bilingual approach. For linguistic pluralism, Singapore justifies an equitable response to the multilingual condition because of fewer languages, and all of these are dominant languages. Meanwhile, Timor-Leste is balancing the languages by strengthening the official languages and preserving the minor languages. In internationalization, both countries recognize the importance of foreign language in their constitution to advance internationalization and incorporate development through glocalization. It appears that Singapore has more of an advantage in comparison, probably due to discovering a suitable language policy that addresses the needs of the nation. On the other hand, Timor-Leste as a young nation is critically strategizing the best policy it could have. Perhaps, one nation can learn from another’s struggles as a benchmark. Certainly, no framework could be utilized in making perfect language policy because it is formed based on the nation’s social, political, and historical background.